2015
DOI: 10.1002/ghg.1523
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical modeling of CO2 leakage in the vadose zone

Abstract: This study presents the experimental and modeling results of CO2 injection and transport in the vadose zone performed in PISCO2 facilities at the ES.CO2 center in Ponferrada (North Spain). During 46 days of experiments, 62.10 kg of CO2 were injected through 16 micro‐injectors in a 35 m3 experimental unit filled with sandy material. Monitoring and mapping of surface CO2 flux were performed periodically to assess the evolution of CO2 migration through the soil and to the atmosphere. Numerical simulations were ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…According to Norstadt [1984], Xu and Qi [2001] and Gasparini et al [2015], an increase of ambient temperature increases CO 2 soil fluxes intensity. Instead, for this case study, an inverse correlation is found between CO 2 soil flux and temperature (Figures 9 and 10): the plot and the multiple regression model show that both air T and the horizontal component of wind speed are anti-correlated with carbon dioxide air concentration, and is clearly visible how CO 2 concentration increases when temperature and wind speed drop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Norstadt [1984], Xu and Qi [2001] and Gasparini et al [2015], an increase of ambient temperature increases CO 2 soil fluxes intensity. Instead, for this case study, an inverse correlation is found between CO 2 soil flux and temperature (Figures 9 and 10): the plot and the multiple regression model show that both air T and the horizontal component of wind speed are anti-correlated with carbon dioxide air concentration, and is clearly visible how CO 2 concentration increases when temperature and wind speed drop.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant uncertainty for the input data implementation in the numerical model. As indicated in Gasparini et al [2015], atmospheric pressure variations over a leakage gas site can move up or delay the emission from soil to atmosphere. Nevertheless, no abrupt change in pressure condition happened during measurements.…”
Section: Metereological Datamentioning
confidence: 99%
“…3 m) horizontal well for CO 2 release. Other relevant experiments include the Ginninderra (Australia, 2010), with the longest running injection (up to 80 days); the CO 2 FieldLab in Norway (2011), one of the deepest injection wells (20 m, at 45° inclination) and the highest injection rates; the CO 2 ‐Vadose project in France, where CO 2 was injected in a limestone quarry; and the PISCO 2 in Spain, where CO 2 was injected in artificially constructed tanks filled with soil. Further details and information on these experiments, among others, can be found in comprehensive reviews published recently by Ko et al .…”
Section: Introductionmentioning
confidence: 99%
“…The ZERT experiment was modeled using the TOUGH2/EOS7CA software to predict the injection rate and design monitoring strategies . The same code was used to simulate different injection scenarios (injection rates, soil characteristics, weather events) within the PISCO 2 project, and also the injection of nitrogen and CO 2 in the Maguelone site in France (as part of the SIMEx project) . The PHREEQC code was used to model changes in water composition with CO 2 injection and dissolution during the field experiment at the CO 2 FieldLab site in Norway .…”
Section: Introductionmentioning
confidence: 99%
“…Field work is being done and mathematical tools are being developed not only to pass stage‐gates for CCS projects, but also to convince policymakers and the general public of the benefits of CO 2 underground storage at a local level. Examples of such work are given in this issue …”
mentioning
confidence: 99%